Enhanced anaerobic fermentation of waste activated sludge by reverse osmosis brine and composition distribution in fermentative liquid. (December 2020) - Pang, Heliang; Wang, Ling; He, Junguo; Zhang, Pengfei; Yan, Zhongsen; Ma, Yingqun; Nan, Jun
Highlights: RO brine enhanced sludge solubilization and subsequent anaerobic fermentation. RO brine-enhanced anaerobic fermentation triggered sludge reduction (37.9% of VSS). The nitrogen-free and carbon-abundant organic matters accounted for 82.1% of SCOD. A mechanism of Na + -attack and Ca 2+ &Mg 2+ -skeleton strengthening on EPS was proposed. RO brine-based strategy was proposed with environmental and economic benefits. Abstract: This study reported a "treating waste by waste" strategy to dispose waste activated sludge (WAS), i.e. reverse osmosis (RO) brine-enhanced anaerobic fermentation. RO brine was hazardous by-product from seawater desalination process, which contains numerous Na + . After 4-day RO brine-enhanced anaerobic fermentation at Na + concentration of 0.33 mol/L, 5.0 g/L VSS reduction (37.9% of VSS) was achievable, leading to considerable soluble chemical oxygen demand (SCOD) release of 349.6 mg/g VSS. Acetic acid was predominant component in SCOD (31.1%), followed by propionic, butyric, valeric acids and proteins (14.0–17.6%). Sludge solubilization and SCOD composition in the enhanced anaerobic fermentation with RO brine and NaCl agent were similar, whereas less nutrient release and extracellular polymeric substance (EPS) disruption were achieved by RO brine, attributing to the Ca 2+ &Mg 2+ -caused skeleton strengthening on EPS matrix. Such RO brine-based strategy provided environmental and economic benefits, e.g. none chemical consumption, synchronous disposal of WAS and RO brine.